A reference proteomic database of Lactobacillus plantarum CMCC-P0002. - Li Zhu; Wei Hu; Datao Liu; Wanhong Tian; Gang Yu; Xiankai Liu; Jie Wang; Erling Feng; Xuemin Zhang; Bei Chen; Ming Zeng; Hengliang Wang (PLoS ONE, 2011)
Lactobacillus plantarum is a widespread probiotic bacteria found in many fermented food products. In this study, the whole-cell proteins and secretory proteins of L. plantarum were separated by two-dimensional electrophoresis method. A total of 434 proteins were identified by tandem mass spectrometry, including a plasmid-encoded hypothetical protein pLP9000_05. The information of first 20 highest abundance proteins was listed for the further genetic manipulation of L. plantarum, such as construction of high-level expressions system. Furthermore, the first interaction map of L. plantarum was established by Blue-Native/SDS-PAGE technique. A heterodimeric complex composed of maltose phosphorylase Map3 and Map2, and two homodimeric complexes composed of Map3 and Map2 respectively, were identified at the same time, indicating the important roles of these proteins. These findings provided valuable information for the further proteomic researches of L. plantarum.